High Diversity of Giardia duodenalis Assemblages and Sub-Assemblages in Asymptomatic School Children in Ibadan, Nigeria - Muyideen K. Tijani; Pamela C. Köster; Isabel Guadano-Procesi; Imo S. George; Elizabeth Abodunrin; Adedamola Adeola; Alejandro Dashti; Begoña Bailo; David González-Barrio; David Carmena (Tropical Medicine and Infectious Disease, 2023)
Giardia duodenalis is a significant contributor to the burden of diarrheal disease in sub-Saharan Africa. This study assesses the occurrence and molecular diversity of G. duodenalis and other intestinal parasites in apparently healthy children (n = 311) in Ibadan, Nigeria. Microscopy was used as a screening method and PCR and Sanger sequencing as confirmatory and genotyping methods, respectively. Haplotype analyses were performed to examine associations between genetic variants and epidemiological variables. At microscopy examination, G. duodenalis was the most prevalent parasite found (29.3%, 91/311; 95% CI: 24.3–34.7), followed by Entamoeba spp. (18.7%, 58/311; 14.5–23.4), Ascaris lumbricoides (1.3%, 4/311; 0.4–3.3), and Taenia sp. (0.3%, 1/311; 0.01–1.8). qPCR confirmed the presence of G. duodenalis in 76.9% (70/91) of the microscopy-positive samples. Of them, 65.9% (60/91) were successfully genotyped. Assemblage B (68.3%, 41/60) was more prevalent than assemblage A (28.3%, 17/60). Mixed A + B infections were identified in two samples (3.3%, 2/60). These facts, together with the absence of animal-adapted assemblages, suggest that human transmission of giardiasis was primarily anthroponotic. Efforts to control G. duodenalis (and other fecal-orally transmitted pathogens) should focus on providing safe drinking water and improving sanitation and personal hygiene practices.